High-k materials in multi-gate FET devices - Tayal, Shubham; Singla, Parveen; Davim, J. Paulo 1964- (CRC Press, Taylor & Francis Group, 2021)
Cover -- Half Title -- Series Page -- Title Page -- Copyright Page -- Table of Contents -- Preface -- Editors -- Contributors -- Chapter 1: Introduction to Multi-Gate FET Devices -- 1.1 Introduction -- 1.2 Double-Gate Devices -- 1.3 Triple-Gate MOSFET Devices -- 1.4 FINFET Characteristics and Modeling -- 1.5 Surrounding-Gate SOI MOSFETs -- 1.6 Additional Multi-Gate FETs -- 1.7 Materials for Multi-Gate Devices -- 1.7.1 Requirements and Characteristics of Multi-Gate in Devices -- 1.8 Nano-Sheet GAA -- 1.8.1 Nanowire GAA -- 1.8.2 SOI Multi-Gate MOSFET Designs -- 1.9 Gate-All-Around (GAA) Nanowire (NW) MOSFETs -- 1.10 GAA Nanowire (NW) Transistors -- 1.11 Double-Gate versus Tri-Gate FET -- 1.12 MIGFET and FinFET Process Technology -- 1.13 Important Parameters in FinFET -- 1.13.1 Current -- 1.13.2 Corner Effects -- 1.13.3 Sub-threshold Slope -- 1.14 Conclusion -- References -- Chapter 2: High- k Gate Dielectrics and Metal Gate Stack Technology for Advance Semiconductor Devices: An overview -- 2.1 Introduction -- 2.2 Downscaling Issues and High- k Materials Relevance in Microelectronics Industry -- 2.3 Material Chemistry and Requirements for High- k Gate Dielectrics -- 2.3.1 Energy Band Gap, Barrier Height, and Dielectric Constant -- 2.3.2 Large k Value -- 2.3.3 Thermodynamic Stability -- 2.3.4 Kinetic Stability -- 2.3.5 High-Quality Interface and Defects -- 2.4 Oxide Deposition -- 2.4.1 MOCVD -- 2.4.2 ALD -- 2.4.3 PVD -- 2.5 Metal Gates and Their Work Function Requirements -- 2.6 Electrical Behavior/Electrical Characteristics of High- k -Based Devices -- 2.6.1 Flat Band Voltage and Threshold Voltage Control -- 2.6.2 Mobility Degradation -- 2.7 Relevance of High- k Gate Dielectrics with TFET -- 2.8 TFET -- 2.8.1 TFET Device Structure and Operating Principle -- 2.8.2 Applications of TFET -- 2.9 Applications of High- k Materials -- 2.10 Summary
Keywords: High-k-Dielektrikum